Study of anomalous babies of neural tubal defects and their mothers - Bilodi, AK; Gangadhar, MR; Kumari, VV; Shetty, HV (Journal of Institute of Medicine Nepal, 2012)
No abstract available Journal of Institute of Medicine, 2011: 33:1